Identifying the challenges and facilitators of implementing a COPD care bundle. Issue 1 (20th June 2014) - Lennox, Laura; Green, Stuart; Howe, Cathy; Musgrave, Hannah; Bell, Derek; Elkin, Sarah
Abstract : Background: Care bundles have been shown to improve outcomes, reduce hospital readmissions and reduce length of hospital stay; therefore increasing the speed of uptake and delivery of care bundles should be a priority in order to deliver more timely improvements and consistent high-quality care. Previous studies have detailed the difficulties of obtaining full compliance to bundle elements but few have described the underlying reasons for this. In order to improve future implementation this paper investigates the challenges encountered by clinical teams implementing a chronic obstructive pulmonary disease (COPD) care bundle and describes actions taken to overcome these challenges. Methods: An initial retrospective documentary analysis of data from seven clinical implementation teams was undertaken to review the challenges faced by the clinical teams. Three focus groups with healthcare professionals and managers explored solutions to these challenges developed during the project. Results: Documentary analysis identified 28 challenges which directly impacted implementation of the COPD care bundle within five themes; staffing, infrastructure, process, use of improvement methodology and patient and public involvement. Focus groups revealed that the five most significant challenges for all groups were: staff too busy, staff shortages, lack of staff engagement, added workload of the bundle and patient coding issues . The participants shared facilitating factors used to overcome issues including: shifting perceptions to improve engagement, further education sessions to increase staff participation and gaining buy-in from managers through payment frameworks. Conclusions: Maximising the impact of a care bundle relies on its successful and timely implementation. Teams implementing the COPD care bundle encountered challenges that were common to all teams and sites. Understanding and learning from the challenges faced by previous endeavours and identifying the facilitators to overcoming these barriers provides an opportunity to mitigate issues that waste time and resources, and ensures that training can be tailored to the anticipated challenges.